Evaluation of Electrolyte Additives for High-Temperature Polymer Electrolyte Fuel Cells - Mack, Florian; Galbiati, Samuele; Gogel, Viktor; Jörissen, Ludwig; Zeis, Roswitha (ChemElectroChem, 2016)
In this study, perfluoroalkyl phosphonic acids CF3PO3H2 and C2F5PO3H2 are investigated as additives to phosphoric acid to improve the oxygen reduction reaction (ORR) of high-temperature polymer electrolyte (PEM) fuel cells. A comprehensive characterization of acid mixtures composed of 20wt% additive and 80wt% concentrated phosphoric acid is presented, ranging from exsitu measurements to insitu tests in operating high-temperature PEM fuel cells. CF3PO3H2 and C2F5PO3H2 additives exhibit excellent thermal stability and are found to improve the wetting of the electrode. The fuel cell's output power increases consistently (240/270mWcm-2 vs. 180mWcm-2), owing to a decrease in the oxygen reduction reaction charge-transfer resistance.
CRIS-Team Scopus Importer:2023-08-01
Keywords: Anion adsorption; Electrolyte additives; Oxygen reduction reaction; Perfluoroalkyl phosphonic acids; Polymer electrolyte fuel cells